E-content development for visual learners - Osman, Norhayati (2013)
Currently, IT Project Management (ITS 510) subject is taught by using textbook and Powerpoint slides. Due to ineffectiveness of teaching materials, this scenario becomes one of the reason that affects the students’ result. Therefore, this E-learning is developed specifically for Visual Learners to attract their attention in class. To fulfill this project, few objectives are highlighted which are 1) To identify the user requirements of visual learners for E-content, 2) To design an E-content software for visual learners and 3) To develop an E-content software for visual learners. Methodology that has been selected to complete this project is based on the ADDIE Model. ADDIE Model consists of Analysis, Design, Development, Implementation and Evaluation phases. The questionnaires were distributed to get the requirement from visual learner users. This requirement helped in designing and developing the E-content. The researcher compared the results from requirement analysis and development analysis to ensure that the objective of this project is fulfilled and the problem of visual learners is solved. At the end, it gives a lot of benefits to learners where they can access the content everywhere and anytime without time restrictions. For educators, the E-content can help them to improve their teaching styles. Lecturer can use this E-content as an aided tool to teach students in class. This Econtent is also easy to be updated by the lecturer. Finally, future suggestion to enhance the E-content is also stated.